(untitled) (Intent Research Scientific Journal, 2026)
This study aims to uncover the phenomenon of syntactic deviation in Arabic and its impact on meaning construction, through a syntactic-semantic approach that combines analyzing the syntactic structure and elucidating its semantic and pragmatic functions in Arabic texts. The study is based on the hypothesis that syntactic deviation is not considered a departure from grammatical rules, but rather represents a deliberate use of the possibilities of the syntactic system to direct meaning and highlight its focus within discourse. The study adopted the descriptive-analytical method based on tracing patterns of syntactic deviation in Quranic, poetic, and prose texts, and then analyzing them in light of grammatical rules and the requirements of the pragmatic context.